(untitled) (Communications in Computational Physics, 2007)
In this paper, based on the multi-symplecticity of concatenating symplectic Runge-Kutta-Nyström (SRKN) methods and symplectic Runge-Kutta-type methods for numerically solving Hamiltonian PDEs, explicit multi-symplectic schemes are constructed and investigated, where the nonlinear wave equation is taken as a model problem. Numerical comparisons are made to illustrate the effectiveness of our newly derived explicit multi-symplectic integrators.